Satellite spoofing from A to Z: on the requirements of satellite downlink overshadowing attacks - Salkield, E; Szakály, M; Smailes, J; Kohler, S; Birnbach, S; Strohmeier, M; Martinovic, I (Association for Computing Machinery, 2023)
Satellite communications are increasingly crucial for telecommunications, navigation, and Earth observation. However, many widely used satellites do not cryptographically secure the downlink, opening the door for radio spoofing attacks. Recent developments in software-defined radio hardware have enabled attacks on wireless systems including GNSS, which can be effectively spoofed using only cheap hardware available off the shelf. However, these conclusions do not generalize well to other satellite systems such as high data rate backhauls or satellite-to-customer connections, where the spoofing requirements are currently unknown. In this paper, we present a systematic review of spoofing attacks against satellite downlink communications systems. We establish a threat model linking attack feasibility and impact to required budget through real-world experiments and channel simulations. Our results show that nearly all evaluated satellite systems were overshadowable at a distance of 1km in the worst case, for a budget of ~2000 USD or less. We evaluate how the key challenges of antenna directionality, legitimate satellite signal presence, modulation schemes, and receiver saturation can be overcome in practice through antenna sidelobe targeting, overshadowing, and automatic gain control takeover. We also show that, surprisingly, protocols designed to be more robust against channel noise are significantly less robust against an overshadowing attacker. We conclude with a discussion of physicallayer countermeasures specifically applicable to satellite systems which can not be cryptographically upgraded.